Evaluation of the optical, structural, morphological and electronic properties of Rb3Bi2I9 Perovskites films prepared by Sequential Evaporation - G. Gordillo; O.G. Torres; C.A. Celis; M. Reinoso; J I Clavijo (Optical Materials: X)
Toxicity and poor stability remain major barriers to large-scale production of hybrid organic-inorganic lead halide perovskite solar cells. Considering the isoelectronic nature of lead (II) and bismuth (III) ions, stable and non-toxic alternatives for developing photovoltaic devices could potentially be found. Rb3Bi2I9 perovskite films inherently suffer from unavoidable pinhole defects and poor surface morphology, which limit device performance. In this work we explored a dual-source thermal sequential evaporation approach to growth uniform and pinhole-free morphology of Rb3Bi2I9 polycrystalline thin films. The influence of post-deposition annealing in a high-pressure N2 atmosphere on the structural, optical, morphological, and electronic properties of the resulting films was studied experimentally using X-ray diffraction (XRD), optical spectrophotometry, scanning electron microscopy (SEM), and computationally via Density Functional Theory (DFT) calculations. The results revealed that post deposition annealing significantly improves both the morphology and degradation processes of Rb3Bi2I9 films, when they are exposed to environmental conditions for long periods of time.